(untitled) (Journal of Informatics Education and Research, 2025)
The bibliometric analysis of employee well-being literature highlights key insights that can contribute to India’s journey toward a prosperous and resilient future. As India strives to emerge as a global leader by 2047, understanding and enhancing employee well-being will be crucial in building a workforce that thrives in the face of rapid technological advancements, global competition, and evolving organizational structures. This study analyzed 707 articles from the Scopus database, using VOS Viewer to map significant trends, gaps, and contributions in the field. Key themes such as job satisfaction, organizational practices, psychological empowerment, emotional labor, and social psychology were identified, offering actionable insights for fostering holistic well-being in India’s growing workforce. With Australia and the United Kingdom leading in citations and publications, India can learn from these countries and tailor strategies that suit its unique socio-economic landscape. The influential work of Guest David in linking human resource management to corporate performance and employee well-being provides a foundation for shaping HR policies in India’s public and private sectors. This study underscores the need for institutions, policymakers, and business leaders in India to focus on employee well-being as a cornerstone for long-term organizational success. By incorporating global best practices and contextualizing them to India’s aspirations, this research aids in the development of strategies to cultivate a healthy, motivated, and resilient workforce—critical for driving India’s economic and social transformation on the global stage.